Diversity of the genus Sargassum (Fucales: Sargassaceae) in Tho Chu Archipelago, Kien Giang Province - Tu, Nguyen Van (Academia Journal of Biology, 2020)
Our study investigated 12 study sites in four main islands of Tho Chu archipelago in 2019. Six Sargassum species were recorded for the flora of Tho Chu Archipelago are Sargassum aquifolium (Turner) C.Agardh, Sargassum feldmannii Pham-Hoang Ho, Sargassum ilicifolium (Turner) C.Agardh, Sargassum mcclurei Setchell, Sargassum oligocystum Montagne, Sargassum polycystum C.Agardh. Among these species, the Sargassum oligocystum Montagne, Sargassum feldmannii Pham-Hoang Ho and Sargassum mcclurei Setchell were newly recorded for West Sea of Vietnam. There was a significant difference in species composition between Tho Chu, Hon Xanh, Hon Tu and Hon Cao islands; among them, Hon Xanh island differed from the other three islands by 28%, Hon Tu island and Tho Chu island were mostly similarity in flora composition with the similarity index of 85.7%. The morphology of some Sargassum species varied by ecological characteristics, especially for Sargassum aquifolium (Turner) C. Agardh and Sargassum oligocystum Montagne.